'Nations, Nationalities, and Peoples': The Ethnopolitics of Ethnofederalism in Ethiopia. Issue 3 (27th May 2017) - Erk, Jan
Abstract: This introductory chapter to the collection on Ethiopian ethnofederalism takes stock of the last 20 years of ethnic federalism in Ethiopia and distils lessons and insights for a broader international/comparative readership. The aim is to set the Ethiopian case within the broader perspective of ethnic politics and federalism—both for scholars and practitioners. And in doing so, it is not the formal aspects of the 1995 federal constitution that take the centre-stage. Instead, what guides the chapters of the collection is the complex workings of ethnic federalism and ethnic politics; especially when the formal meets the uncodified.